"Izrekam zvestobo moji novi domovini Republiki Sloveniji ---" - Ferbežar, Ina (Jezik in slovstvo, 2012)
The article presents the status of speakers of Slovene as a second and foreign language, especially those who are required to demonstrate their competence in Slovene with an official certificate in order to be able to live and work in the Republic of Slovenia. According to data for recent years, the number of immigrants in Slovenia is increasing, as are the formal language requirements. Competence in Slovene language has been a condition for acquiring Slovene citizenship by naturalisation since 1992, while it is only in the past few years that other countries of the European Union have started to introduce language exams for so-called integration purposes. Language testing for citizenship purposes affects some fundamental human rights, and thus raises numerous ethical issues as well as issues of access to language skills, teaching practices and the actual communication needs of the test takers. On the other hand, a problem has been identified in those areas where the language requirements should be more clearly defined; for example, regarding foreign medical doctors seeking employment in Slovenia. In the second part, the article focuses on the current system of testing Slovene as asecond and foreign language, providing some statistics on the number of test takers, their origins, learning practices and reasons for sitting Slovene language exams. Most importantly, the article raises some important questions regarding language exams for specific groups of speakers whose mother tongues are closely related to Slovene.
Keywords: Slovene; slovenski jezik; slovenščina kot drugi/tuji jezik; jezikovna politika; testiranje; državljanstvo